Janns laptop standger / Nurul Akma An Najwa Ramli … [et al.] - Ramli, Nurul Akma An Najwa; Mohd Rafi, Alifah Ilyana; Laser, Jassinta; Mohd Fadzilla, Nur Syahira; Mohd Adaha, Siti Sarah; Omar, Siti Nazirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Advances in technology have bribed new lifestyles in addition to dynamic consumer tastes. The problem with the traditional laptop charger, its heavy and messy components lack mobility and takes a long time to charge as well as easily can be damaged over time. Moreover, wireless chargers in the market still are not able to maximize the needs of users in one product. Our objective is to offer the users greater convenience that they could not have while using the traditional charger, reduce risk, less damage, and a more organized workplace. Therefore, JANNS Laptop Standger is designed to meet the needs of solving those problems. From the use of material and advanced components to its on-the-go function, we ensure that JANNS Laptop Standger is of top-notch quality so that it will always bring benefit to others. JANNS Laptop Standger is expected to give impact those who utilize a computer in their daily lives. They could do their jobs anytime and anywhere without worrying about where they are going to charge their laptop. Besides, industrial production in Malaysia is forecast to outpace economic growth by 6.9% in 2022 before increasing to 5.8% growth in 2023 (Industry - Country Industry Forecasts - Malaysia, n.d.). After SWOT analysis in this COVID-19 situation, seemingly, the strength of this product is the package of functionality itself and very potential for golden opportunities to grow bigger such as partnering with a well-known electrical company.